"It doesn't matter how good the school is if you don't learn to socialize": Latinx immigrant students' testimonios of coping with social isolation in high school. (June 2022) - Lilly, Jenn M.
Abstract: Understanding how Latinx immigrant youth cope with the stressor of social isolation is vital to understanding and improving their functioning and well-being; yet little is known about how they cope with experiences of social isolation in school. To fill this gap in the literature, the purpose of this exploratory study was to qualitatively examine the coping strategies that Latinx immigrant students utilized in the face of social isolation in one high school in a newer Latinx destination in the U.S. south. This study employed a narrative and culturally-congruent methodological approach, analyzing the digital testimonios of 5 female and 2 male Latinx young people, age 17–22. Latinx immigrant youth's coping styles are theoretically interpreted using Endler's (1997) multidimensional interaction model of stress, anxiety, and coping processes, which delineates three coping styles: task-oriented, emotion-oriented, and avoidance-oriented. Findings demonstrate that participants used a range of both emotion-oriented (including self-kindness, problem reframing, expressing emotion, self-blame, and seeking emotional support) and task-oriented (information-seeking and direct-action) strategies to cope with social isolation. Emotion-oriented strategies were featured more prominently than task-oriented coping in Latinx immigrant students' narratives of coping with social isolation, and avoidance-oriented coping styles were not described. These findings highlight the importance of emotion-oriented coping for Latinx immigrant youth and illustrate the need for interventions that enhance coping skills and policies to prevent and ameliorate social isolation and thereby improve the socio-emotional well-being of Latinx immigrant students.